PENGARUH PENERAPAN METODE GAME BASED LEARNING (BAAMBOOZLE) SEBAGAI MEDIA EVALUASI TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA KELAS V DI SD NEGERI 128 PEARUNG-HUMBAHAS - Sinaga, Elisabeth R L; Ginting, Sita Verbina Br. (Unversitas Katolik Santo Thomas, 2025)
This research aims to determine the influence of media application Baamboozle learning as a media for eval_uating students' English learning outcomes at SD Negeri 128 Pearung-Humbahas. The sample in this study was class V with a total of 28 students. The research instrument uses observation and tests. Data collection methods use observation sheets, test sheets and documentation. The data analysis techniques used are descriptive statistical analysis techniques and inferential statistics. Based on the results of research and data analysis regarding statistical value comparisons and comparisons of learning outcome categories, it has been proven that there is an increase in student learning outcomes in English subjects after implementing game based learning (Baamboozle) so that it can be used as a learning eval_uation medium that is able to increase student activity and enthusiasm. and provide a positive response to the learning media. It can be seen from student learning outcomes through descriptive statistical analysis that before using Baamboozle media the average student score is still in the low interval category and after using Baamboozle media the average student score is in the high interval category significantly. It is known that the average score of students' Pretest results is 38.32 and the average score of students' Posttest results is 72.32, where the Posttest score is greater than the Pretest score. Furthermore, based on the results of inferential statistical analysis using the t-test formula, it is known that the t-count obtained is 29-92 with a frequency of df= 28-1=27, at a significance level of 0.05 or 5% the t table is 1.703. So t-count > ttable or H0 is rejected and H1 is accepted. From the results of these data it can be concluded that by applying the Baamboozle media in learning, especially in eval_uating the learning of class V students in the English subject at SD Negeri 128 Pearung-Humbahas, they gave a positive response to this learning media.